2010
DOI: 10.1093/humrep/deq278
|View full text |Cite
|
Sign up to set email alerts
|

DNA integrity, growth pattern, spindle formation, chromosomal constitution and imprinting patterns of mouse oocytes from vitrified pre-antral follicles

Abstract: DNA breaks appear to be rapidly repaired and vitrification of oocytes inside pre-antral follicles by the Cryo-Top method does not appear to increase risks of abnormal imprinting or disturbances in spindle formation and chromosome segregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 107 publications
9
73
1
2
Order By: Relevance
“…Using long-term IVM and supraphysiological recombinant FSH (rFSH), imprinted methylation perturbations were observed in pools of GV oocytes with H19 GOM (1/7 pools), Peg1 LOM (1/7 pools), and Igf2r LOM (6/7 pools) (Kerjean et al 2003; Table 2). By comparison, normal H19 (0/39 strands) and Igf2r methylation (0/15 strands) was found in pooled GV oocytes following longterm IVM with physiological rFSH, although LOM was observed at Snrpn (2/47 DNA strands) (Trapphoff et al 2010). Additionally, independent studies with long-term IVM using physiological or supraphysiological rFSH reported normal Snrpn, Igf2r, Peg3, and H19 methylation in MII oocyte pools (Anckaert et al 2009a(Anckaert et al , 2009b(Anckaert et al , 2010.…”
Section: In Vitro Oocyte Maturationmentioning
confidence: 90%
See 1 more Smart Citation
“…Using long-term IVM and supraphysiological recombinant FSH (rFSH), imprinted methylation perturbations were observed in pools of GV oocytes with H19 GOM (1/7 pools), Peg1 LOM (1/7 pools), and Igf2r LOM (6/7 pools) (Kerjean et al 2003; Table 2). By comparison, normal H19 (0/39 strands) and Igf2r methylation (0/15 strands) was found in pooled GV oocytes following longterm IVM with physiological rFSH, although LOM was observed at Snrpn (2/47 DNA strands) (Trapphoff et al 2010). Additionally, independent studies with long-term IVM using physiological or supraphysiological rFSH reported normal Snrpn, Igf2r, Peg3, and H19 methylation in MII oocyte pools (Anckaert et al 2009a(Anckaert et al , 2009b(Anckaert et al , 2010.…”
Section: In Vitro Oocyte Maturationmentioning
confidence: 90%
“…Ultra-rapid vitrification of mouse preantral follicles followed by long-term IVM to GV oocytes led to Snrpn LOM (1/50 strands) but not Igf2r LOM (0/15 strands) or H19 GOM (0/58 strands) in pooled vitrified oocytes (Trapphoff et al 2010). In the second study, mice produced following whole ovary cryopreservation maintained normal H19 and Kcnq1ot1 methylation ratios (Sauvat et al 2008).…”
Section: Analysis Of Imprinting Stability During Artsmentioning
confidence: 94%
“…Some studies have demonstrated that vitrification does not significantly alter gene methylation patterns in oocytes [110,115,119] and blastocysts [112]. In contrast, vitrification has been found to reduce gene methylation in mouse oocytes [113], embryos [112], and fetuses [117].…”
Section: Molecular Effects Of Cryopreservationmentioning
confidence: 99%
“…We have developed two different multiplex assays, each with four genes, for studying imprinted gene methylation in the murine 25 and bovine model, 26 respectively. Outer …”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%